PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUASAN PELANGGAN PADA PERCETAKAN ANEKA JAYA PEMATANGSIANTAR - Agustina, Eva; Lie, Darwin; Butarbutar, Marisi; Nainggolan, Nana Triapnita (Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2019)
The results of this study can be summarized as namely: 1. The quality of the product is good, the customer agrees that the price and satisfaction of the customer are satisfied. 2. Product quality and price have a positive effect on customer satisfaction in Aneka Jaya Pematangsiantar Printing. 3. There is a high and positive relationship between product quality and price to customer satisfaction. Then the high and low customer satisfaction can be explained by product quality and price. 4. H0 hypothesis is rejected, meaning that product quality and price have a positive and significant effect on customer satisfaction in Aneka Jaya Pematangsiantar Printing both simultaneously and partially.Â Keywords: Product Quality, Price and Customer Satisfaction